Parents' pandemic stress, parental involvement, and family quality of life for children with autism - Cheng, Shengli; Cheng, Sanyin; Liu, Shushan; Li, Yun (Frontiers in Public Health, 2022)
Background: Research has shown that parents of children with autism spectrum disorder (ASD) suffered high levels of stress during the COVID-19 pandemic and faced poor family quality of life (FQOL). However, little is known about the inherent dynamic interaction between pandemic stress and FQOL, especially in the Chinese cultural context. Aims: This study provides preliminary evidence by examining the relationships among pandemic stress, parental involvement, and FQOL for children with autism in mainland China. Method: A total of 709 parents of children with autism completed measures of FQOL, parental involvement, and pandemic stress. Structural equation modelling was employed to examine the interrelations among these variables. Results: Pandemic stress has direct effect and indirect effect mediated by parental involvement on FQOL. Two dimensions of pandemic stress had a direct effect on FQOL (β1 = 0.11; β2 = -0.55) and three dimensions had an indirect effect on FQOL through parental involvement (β1 = -0.097; β2 = 0.257; β3 = 0.114). Conclusion: Stress related to the COVID-19 pandemic affects family quality of life for children with autism in complex ways. Policies may be developed to enhance parental pragmatic hopefulness in the anti-epidemic victory and alleviate negative physical and mental reactions caused by the pandemic.